Kemampuan Literasi Statistik dalam Pembelajaran Berbasis Proyek yang Dimodifikasi - Fitri Nur Oktiviani; St. Budi Waluya; Zaenuri (Civiliza Publishing, 2021)
The statistical literacy ability of junior high school students is still low. One way to improve statistical literacy skills is to innovate the applied learning model, namely the modified project-based learning model. The purpose of this study was to analyze the achievement and improvement of statistical literacy skills of students who received modified project-based learning with conventional ones, as well as to find out the interpretation of increasing statistical literacy skills of students from both classes. The method in this research is a quasi-experimental method. The sampling technique was carried out by taking a sample of two classes at Al Musyaffa Middle School, Kendal district using the technique Purposive Sampling. Data analysis was carried out quantitatively using Normalized Gain Test and Mann Whitney. The results showed that the achievement and improvement of statistical literacy skills of students who received modified project-based learning were better than students who received conventional learning based on modification project have a moderate interpretation while increasing students' statistical literacy skills with conventional learning has a low interpretation.